Management of Pulmonary Hemorrhage Complicating Pulmonary Thromboendarterectomy - Dalia, Adam A.; Streckenbach, Scott; Andrawes, Mike; Channick, Richard; Wright, Cameron; Fitzsimons, Michael (Frontiers in Medicine, 2018)
Airway management during pulmonary thromboendarterectomy (PTE) can prove challenging, especially in the face of unexpected intraoperative pulmonary hemorrhage. Utilization of proper airway equipment on induction is crucial for the successful management of intraoperative pulmonary hemorrhage. Our case series describes the preoperative risk factors that can lead to intraoperative pulmonary hemorrhage, the preinduction airway equipment considerations for PTE, and the intraoperative management of pulmonary hemorrhage. We summarize the lessons learned at our institution from four cases of post perfusion pulmonary hemorrhage.